2012
DOI: 10.1017/s0305000912000396
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of orthographic support for oral vocabulary learning in children with Down syndrome

Abstract: Copyright - Cambridge University PressChildren with Down syndrome typically have weaknesses in oral language, but it has been suggested that this domain may benefit from learning to read. Amongst oral language skills, vocabulary is a relative strength, although there is some evidence of difficulties in learning the phonological form of spoken words. This study investigated the effect of orthographic support on spoken word learning with seventeen children with Down syndrome aged seven to sixteen years and twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…In the remainder of this Does orthography support oral vocabulary learning for children with ASD? Vocabulary learning is facilitated by the presence of orthography for TD children (Reitsma, 1983;Ricketts et al, 2009;Rosenthal & Ehri, 2008) and children with Down syndrome (Mengoni et al, 2013). The present study extends these findings by demonstrating for the first time that this is also the case for children with ASD who had developed proficient phonological decoding and singleword reading skills.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In the remainder of this Does orthography support oral vocabulary learning for children with ASD? Vocabulary learning is facilitated by the presence of orthography for TD children (Reitsma, 1983;Ricketts et al, 2009;Rosenthal & Ehri, 2008) and children with Down syndrome (Mengoni et al, 2013). The present study extends these findings by demonstrating for the first time that this is also the case for children with ASD who had developed proficient phonological decoding and singleword reading skills.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, previous research has demonstrated that regular words are learned more readily than irregular words (Wang, Castles, & Nickels, 2012), though orthography is most beneficial for learning new words with irregular spellings (Ricketts et al, 2009, but see Rastle, McCormick, Bayliss, & Davis, 2011. We did not control for regularity in the present study; to provide such a control would require use of nonword stimuli, as employed by Ricketts et al (2009) and Mengoni et al (2013). Given the educational challenges that children with ASD face, we felt it would be more beneficial to see whether we could support learning of words that had scholastic relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, on a more specific level, the finding of longitudinal stability in language and verbal short-term memory skills in children with Down syndrome suggests that intervention to improve language learning in these children may be particularly important from an early age. There is evidence that early high-frequency language intervention for children with Down syndrome can result in significant gains in vocabulary (Yoder, Woynaroski, Fey, & Warren, 2014), and evidence also suggests that learning to read may help to promote their language development (Buckley & Bird, 1993;Burgoyne et al, 2012;Mengoni, Nash, & Hulme, 2013;Oelwein, 1995). However, although such approaches may appear to be promising, few experimental language training studies including children with Down syndrome exist, and the transfer effect to items not trained remains unclear.…”
Section: Discussionmentioning
confidence: 99%